Estimation of the design elements of horizontal alignment by the method of least squares/Jalina Rabi - Rabi, Jalina (Faculty of Civil Engineering, 2006)
Although the construction of highway takes place in three dimensional spaces, the procedures that govern their design have been developed within 3 separate sets of two dimensional relationship that represent the plan, profile, and cross-section view. The plan view encompasses the horizontal alignment of the road in the x-y plan. This study focused only on horizontal road alignment where the road linear shape is sampled centerline path and deduced using Least Square Method to estimate the design element of the road curve under studied. The results were analyzed and compared with the existing road element in the design.